AN ANALYSIS FORM AND MEANING OF ONOMATOPOEIA IN “EGGNOID” DIGITAL COMIC - Zulaikah Zulaikah; Satria Andrianto; Reni Reni; Iis Juliana (IKIP Siliwangi, 2024)
This research describes the types of violations found in the film